Tempo and mode of regulatory evolution in Drosophila - Coolon, Joseph D.; McManus, C. Joel; Stevenson, Kraig R.; Graveley, Brenton R.; Wittkopp, Patricia J.

(untitled) (Genome Research, 2014)
Genetic changes affecting gene expression contribute to phenotypic divergence; thus, understanding how regulatory networks controlling gene expression change over time is critical for understanding evolution. Prior studies of expression differences within and between species have identified properties of regulatory divergence, but technical and biological differences among these studies make it difficult to assess the generality of these properties or to understand how regulatory changes accumulate with divergence time. Here, we address these issues by comparing gene expression among strains and species of Drosophila with a range of divergence times and use F1 hybrids to examine inheritance patterns and disentangle cis- and trans-regulatory changes. We find that the fixation of compensatory changes has caused the regulation of gene expression to diverge more rapidly than gene expression itself. Specifically, we observed that the proportion of genes with evidence of cis-regulatory divergence has increased more rapidly with divergence time than the proportion of genes with evidence of expression differences. Surprisingly, the amount of expression divergence explained by cis-regulatory changes did not increase steadily with divergence time, as was previously proposed. Rather, one species (Drosophila sechellia) showed an excess of cis-regulatory divergence that we argue most likely resulted from positive selection in this lineage. Taken together, this work reveals not only the rate at which gene expression evolves, but also the molecular and evolutionary mechanisms responsible for this evolution.